Soil uses during the sugarcane fallow period: influence on soil chemical and physical properties and on sugarcane productivity - Silva, Roniram Pereira Da [UNESP]; Fernandes, Carolina [UNESP] (Sociedade Brasileira de Ciência do Solo, 2014)
The planting of diversified crops during the sugarcane fallow period can improve the chemical and physical properties and increase the production potential of the soil for the next sugarcane cycle. The primary purpose of this study was to assess the influence of various soil uses during the sugarcane fallow period on soil chemical and physical properties and productivity after the first sugarcane harvest. The experiment was conducted in two areas located in Jaboticabal, São Paulo State, Brazil (21º 14' 05'' S, 48º 17' 09'' W) with two different soil types, namely: an eutroferric Red Latosol (RLe) with high-clay texture (clay content = 680 g kg-1) and an acric Red Latosol (RLa) with clayey texture (clay content = 440 g kg-1). A randomized block design with five replications and four treatments (crop sequences) was used. The crop sequences during the sugarcane fallow period were soybean/millet/soybean, soybean/sunn hemp/soybean, soybean/fallow/soybean, and soybean. Soil use was found not to affect chemical properties and sugarcane productivity of RLe or RLa. The soybean/millet/soybean sequence improved aggregation in the acric Latosol.

A diversificação de culturas, no período de reforma do canavial, pode contribuir para a melhoria dos atributos químicos e físicos do solo, incrementando seu potencial produtivo para o próximo ciclo da cana-de-açúcar. O objetivo deste trabalho foi avaliar a influência de diferentes usos do solo, no período de reforma do canavial, nos atributos químicos e físicos do solo e na produtividade da cana-de-açúcar, avaliados após o primeiro corte. O experimento foi conduzido em duas áreas localizadas no município de Jaboticabal, SP (21º 14' 05'' S e 48º 17' 09'' W), em um Latossolo Vermelho eutroférrico (LVef) textura muito argilosa (argila = 680 g kg-1) e um Latossolo Vermelho ácrico (LVw) textura argilosa (argila = 440 g kg-1). O delineamento experimental foi em blocos casualizados com cinco repetições e quatro tratamentos, caracterizados por diferentes usos do solo no período de reforma do canavial (soja/milheto/soja, soja/crotalária/soja, soja/pousio/soja e soja). Os diferentes usos do solo não influenciaram os atributos químicos do solo e a produtividade da cana-de-açúcar no LVef e no LVw. O uso soja/milheto/soja favoreceu a agregação do LVw.
Usos do solo no período da reforma do canavial: atributos químicos e físicos do solo e produtividade da cana-de-açúcar
Keywords: crop diversification; Soybean; millet; sunn hemp; diversificação de culturas; Soja; Milheto; Crotalária